Sagot :
Answer:
[tex] - x - 2y = - 10 \: \: and \: \: 2x + y = - 1[/tex]
pick only 1 to be substituted:
[tex] - x - 2y = - 10[/tex]
[tex] - x = - 10 + 2y[/tex]
[tex]x = 10 - 2y[/tex]
substitute the value of x = 10 - 2y to 2x + y = -1
[tex]2(10 - 2y) + y = - 1[/tex]
[tex]y = 7[/tex]
so, we got the value of y; substitute it to get the value of x:
[tex]x = 10 - 2y[/tex]
[tex]x = 10 - 2(7)[/tex]
[tex]x = 10 - 14[/tex]
[tex]x = - 4[/tex]
so, the solution is:
[tex]x = - 4 \: \: || \: \: y = 7[/tex]
or
( x , y ) = ( -4 , 7 )
#CarryOnLearning